Vloga fukozil- in sialiltransferaz pri rakavih obolenjih in procesu metastaziranja - Čuš, Tilen (Farmacevtski vestnik, 2025)
Cancer is one of the leading causes of mortality in the developed world, with 90% of cancer-related deaths being associated with metastasis. This is a complex process involving numerous biochemical changes, including alterations in cellular glycosylation – particularly sialylation and fucosylation. In this process, sialyl- and fucosyltransferases are central enzymes that catalyze the attachment of sialic acid and fucose to their corresponding substrates. Changes in their expression can be observed in various cancers, where they may lead to alterations in cell adhesion, proliferation, motility, tumor angiogenesis, and immune system evasion, significantly enhancing the metastatic potential of cancer cells. Additionally, their increased activity is linked to various types of cancer, such as breast, colon, and pancreatic cancers. Understanding their role in both physiological and pathological conditions offers new possibilities for innovative approaches in cancer treatment and diagnosis,
Keywords: fukoziltransferaze; glikozilacija; Metastaziranje; Rak (medicina); sialiltransferaze